2003
DOI: 10.1055/s-2003-41801
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin is Released from Rat Hypothalamic Explants and Stimulates Corticotrophin-releasing Hormone and Arginine-vasopressin

Abstract: Ghrelin and synthetic growth hormone secretagogues have diverse effects on the hypothalamus including effects on appetite and the growth hormone axis as well as on the hypothalamus-pituitary-adrenal (HPA) axis. We previously studied the effect of synthetic growth hormone secretagogues on CRH and AVP release from rat hypothalami in vitro, and now report on the effects of ghrelin on CRH and AVP release. The ghrelin protein content and ghrelin output from rat hypothalamic explants was measured using a specific no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…This is consistent with observations that ghrelin affects synaptogenesis and development of neuronal circuits, as well as modulation of memory processes, sleep patterns and behavior [44,45,46,47,48,49,94,95,96]. Within the hypothalamus-pituitary axis, GHS-R1a mediates ghrelin/GHS modulation of GH, PRL, CRH/ACTH and GnRH/gonadotropin secretion [26,27,28,97,98,99,100,101,102]. Orexigenic effects of ghrelin/GHS are likely mediated by GHS-R1a expressed by hypothalamic neurons containing neuropeptide Y (NPY)/Agouti-related protein [34,103,104,105,106].…”
Section: Type 1a Ghs Receptorsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with observations that ghrelin affects synaptogenesis and development of neuronal circuits, as well as modulation of memory processes, sleep patterns and behavior [44,45,46,47,48,49,94,95,96]. Within the hypothalamus-pituitary axis, GHS-R1a mediates ghrelin/GHS modulation of GH, PRL, CRH/ACTH and GnRH/gonadotropin secretion [26,27,28,97,98,99,100,101,102]. Orexigenic effects of ghrelin/GHS are likely mediated by GHS-R1a expressed by hypothalamic neurons containing neuropeptide Y (NPY)/Agouti-related protein [34,103,104,105,106].…”
Section: Type 1a Ghs Receptorsupporting
confidence: 90%
“…Ghrelin was shortly identified as a motilin homologue or the ‘motilin-related polypeptide’ [22, 23], which had been found capable of stimulating gut motility [24, 25]. Since this time, numerous other neuroendocrine effects have been attributed to ghrelin, such as stimulation of CRH, ACTH, PRL secretion and inhibition of GnRH and gonadotropin release [26,27,28]. In addition, non-endocrine and metabolic activities of ghrelin have also been described, notably stimulation of food intake and gut motility [27,29,30,31,32,33], influences on body weight and energy balance [34], insulin release, glucose and lipid metabolism [35,36,37,38,39,40,41,42,43], sleep [44, 45], behavioral responses to stress [46,47,48], learning and memory [49], improvements of cardiovascular performances [50,51,52,53,54], effects on cell proliferation, differentiation, survival and fetal development [55,56,57,58,59,60,61], besides influencing immunological responses [[62], see also for reviews [63,64,65,66]].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin stimulates the HPA axis in the rat directly and by stimulation of both CRH, and arginine vassopresin (AVP) release from the hypothalamus (Mozid et al 2003). At the pituitary level, we have demonstrated (Stevanović et al 2006), in agreement with others (Wren et al 2000;Arvat et al 2001), that centrally administered ghrelin stimulated both pituitary adrenocorticotrophic hormone (ACTH) and corticosterone secretion.…”
Section: Introductionsupporting
confidence: 89%
“…Furthermore, repeated [50,51,52] but inconsistent [53] findings indicate that ghrelin, being not only a link between the nervous and endocrine systems but also part of a circuit relevant in depression [54] and crucially involved in sleep regulation [55], increases noradrenergic transmission in the hypothalamus, supporting an antidepressant action; decreased central monoaminergic function is an established hypothesis for the etiopathogenesis of depression [54]. In contrast, ghrelin’s suppressive effect on central release of another monoamine, namely serotonin [53], suggests a depressogenic effect, such as its stimulatory action on the hypothalamic-pituitary-adrenal axis [56,57,58,59]; hyperactivity of the hypothalamic-pituitary-adrenal axis is another model for the development of depression [59]. We also reported that an antidepressant-like effect of antisense DNA for ghrelin in rats suggests a depressogenic effect [42].…”
Section: Discussionmentioning
confidence: 99%